Camel Milk Modulates the Expression of Aryl Hydrocarbon Receptor-Regulated Genes, Cyp1a1,Nqo1, and Gsta1, in Murine hepatoma Hepa 1c1c7 Cells. - Korashy, Hesham M.; El Gendy, Mohamed A. M.; Alhaider, Abdulqader A.; El-Kadi, Ayman O. (Journal of Biomedicine & Biotechnology, 2012)
There is a traditional belief in the Middle East that camel milk may aid in prevention and treatment of numerous cases of cancer yet, the exact mechanism was not investigated. Therefore, we examined the ability of camel milk to modulate the expression of a well-known cancer-activating gene, Cytochrome P450 1a1 (Cyp1a1), and cancer-protective genes, NAD(P)H:quinone oxidoreductase 1 (Nqo1) and glutathione S-transferase a1 (Gsta1), in murine hepatoma Hepa 1c1c7 cell line. Our results showed that camel milk significantly inhibited the induction of Cyp1a1 gene expression by 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD), the most potent Cyp1a1 inducer and known carcinogenic chemical, at mRNA, protein, and activity levels in a concentration-dependent manner. In addition, camel milk significantly decreased the xenobiotic responsive element (XRE)-dependent luciferase activity, suggesting a transcriptional mechanism is involved. Furthermore, this inhibitory effect of camel milk was associated with a proportional increase in heme oxygenase 1. On the other hand, camel milk significantly induced Nqo1 and Gsta1 mRNA expression level in a concentration-dependent fashion. The RNA synthesis inhibitor, actinomycin D, completely blocked the induction of Nqo1 mRNA by camel milk suggesting the requirement of de novo RNA synthesis through a transcriptional mechanism. In conclusion, camel milk modulates the expression of Cyp1a1, Nqo1, and Gsta1 at the transcriptional and posttranscriptional levels.